Analysis of the sixth objective of the Global Agenda 2030 and the Legal Framework for Basic Sanitation: documentary study (Revista Científica Integrada, 2023)
Objective: analyze the goals of the sixth Sustainable Development Goal and relate them to the guidelines presented in the Legal Framework for Basic Sanitation. Methods: this is a documentary study, with a qualitative approach, carried out between August and December 2022, based on the analysis of data collected in the secondary study. Results: the 2030 Agenda is considered one of the most relevant challenges of the 21st century, as it is extremely important for the country, capable of stimulating policies in addition to promoting health and promoting human dignity. Conclusion: knowledge, compliance with legislation, incentives, management, technology, and investments are necessary to achieve sustainable development objectives in all contexts.
Keywords: Sanitation; Sustainable Development Goals; Quality of life